An Anthology of Asemic Handwriting - Gaze, Tim; Jacobson, Michael (punctum books, 2013)
An Anthology of Asemic Handwriting is the first book-length publication to collect the work of a community of writers on the edges of illegibility. Asemic writing is a galaxy-sized style of writing, which is everywhere yet remains largely unknown. For human observers, asemic writing may appear as lightning from a storm, a crack in the sidewalk, or the tail of a comet. But despite these observations, asemic writing is not everything: it is just an essential component, a newborn supernova dropped from a calligrapher's hand. Asemic writing is simultaneously communicating with the past and the future of writing, from the earliest undeciphered writing systems to the xenolinguistics of the stars; it follows a peregrination from the preliterate, beyond the verbal, finally ending in a postliterate condition in which visual language has superseded words. An Anthology of Asemic Handwriting is compiled and edited by Tim Gaze from Asemic magazine and Michael Jacobson from The New Post-Literate blog.